Enhancing daily living and cognitive functions in traumatic brain injury patients through Orem’s self-care theory - Sha, Pei; Gao, Xing; Yu, Ran; Li, Ying; Zhang, Yameng; Zhu, Ziyu; Wu, Ting; Liu, Chang (Frontiers in Neurology, 2024)
Introduction This research seeks to investigate how early rehabilitation nursing, guided by Orem’s self-care theory, affects cognitive function, neurological function, and daily living skills in individuals who have suffered a traumatic brain injury (TBI). Methods A study was conducted with 108 patients with traumatic brain injury who were hospitalized at our facility from January 2021 to March 2023. Based on their admission dates, the participants were separated into a control group (n = 56) and an observation group (n = 52). The control group received standard nursing care, while the observation group received a combination of conventional treatment and nursing interventions based on Orem’s self-care model. The research assessed alterations in the ability to perform daily tasks (Activities of Daily Living, ADL), neurological health (National Institutes of Health Stroke Scale, NIHSS; Glasgow Coma Scale, GCS), and cognitive abilities (Montreal Cognitive Assessment Scale, MoCA; Mini-Mental State Examination, MMSE) in both sets of participants prior to and following 4 and 8 weeks of nursing assistance. Results Following the intervention, the group being observed showed notably increased ADL scores at 4 weeks (p < 0.001) and 8 weeks (p < 0.001) in comparison to the control group. At 4 weeks and 8 weeks after nursing, the observation group had significantly lower NIHSS scores compared to the control group (4 weeks after nursing, p = 0.03; 4 weeks after nursing, p < 0.001). GCS score comparison showed the similar results (4 weeks after nursing, p = 0.013; 4 weeks after nursing, p = 0.003). Moreover, the participants in the observation group had notably higher MoCA and MMSE scores in comparison with the control group 4 and 8 weeks after nursing (all p < 0.001). Conclusion Orem’s self-care theory improves patients’ cognitive, neurological, and daily living functions of TBI patients during early rehabilitation nursing. This method helps enhance the level of care given by healthcare professionals, leading to more thorough and compassionate nursing care for patients.